A study of Immunoglobulins,Complements and Some Hematological Parameters Levels in Thalassemic Patients in Related Bacterial Infections - Samira N AL-Naim; Zena K Khalil; Saif S Al-Kamel (Diyala Journal of Medicine, 2018)
Background: Thalassemia and abnormal hemoglobin are the most common genetic disorders and are considered health problems in many developing countries. Beta-Thalassemia major is the most familiar type, in which the beta-globin chain synthesis is impaired.